Covid‐19 First Wave Impact National Survey for HIV Clinicians by Public Health England (PHE), the British HIV Association (BHIVA) and the Children's HIV Association (CHIVA). Issue 10 (28th March 2022) - Shanks, Gabriella; Shah, Ammi; Williams, Amanda; Asboe, David; Anderson, Jane; Delpech, Valerie; Ely, Amanda; Waters, Laura
Abstract: Introduction: This short report describes the results of a survey that was developed by Public Health England (PHE), the British HIV Association (BHIVA) and the Children's HIV Association (CHIVA) and circulated to all UK national health service HIV providers in the UK following the first wave of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2; coronavirus disease 2019 [COVID‐19]) pandemic to assess the impact of the pandemic on HIV clinics. Methods: The survey was created by BHIVA/CHIVA and PHE and was piloted prior to circulation to all HIV clinics within the UK on 3 July 2020. The survey questions were designed to assess the impact of the first wave of COVID‐19 on HIV clinics and lead/senior HIV clinicians. Clinicians' responses were collected between 3 July 2020 and 17 September 2020. The survey responses were collated, and non‐statistical analysis was performed. Results: The results of the survey confirmed that services had undergone substantial changes, including a shift from face‐to‐face consults to predominantly virtual consultations. Some clinicians' responses suggested that the first wave had many negative effects on people living with HIV, including their ability to access mental health services. Conclusion: The first wave of COVID‐19 caused significant changes to HIV services within the UK. There was a shift toward the use of technology in healthcare, and results from subsequent clinician surveys carried out since the first wave of COVID‐19 will reflect the ongoing transformation of care towards a more virtual service.